Flash-forwards as a figurative mechanism of suicidal risk: a clinical and theoretical analysis - Anna B. Iakovleva; Luiza V. Ryabinina (Transactional Analysis in Russia, 2026)
This article examines the phenomenon of suicidal flash-forwards – intrusive mental images of a future suicide – as a key yet insufficiently recognized factor in suicide risk. Drawing on research by Emily A. Holmes and her colleagues, the article demonstrates that mental imagery has a stronger emotional impact than verbal thoughts and may increase readiness to engage in suicidal action by creating a subjectively experienced “reality of the future”. The article integrates findings from cognitive psychology with concepts from Alfred Adler’s Individual Psychology and transactional analysis, including Robert and Mary Goulding’s ideas on depressive scripts and early decisions, as well as present-day contemporary critique in the works of Tony White. Suicidal flash-forwards are conceptualized as image-bearing expressions of script impasses associated with experiences of helplessness, protest, loss of control, and inability to establish an alternative way of relating to another person. Particular attention is given to the clinical implications, including the need for systematic assessment of suicidal imagery, its role in diagnostic assessment, as well as options for psychotherapeutic work. The article also considers a study evaluating the effectiveness of a cognitive dual-task add-on module involving eye movements, used alongside standard treatment in patients with depressive symptoms and suicidal intrusions. It is concluded that working with mental imagery should be regarded as a central component of suicide prevention, as it offers a means of targeting the mechanisms underlying the transition from suicidal ideation to suicidal action.